More than a feeling? What does compassion in healthcare 'look like' to patients? - Sofie I. Baguley; Alina Pavlova; Nathan S. Consedine (Wiley, 2022)
Abstract Objective Compassion is important to patients and their families, predicts positive patient and practitioner outcomes, and is a professional requirement of physicians around the globe. Yet, despite the value placed on compassion, the empirical study of compassion remains in its infancy and little is known regarding what compassion 'looks like' to patients. The current study addresses limitations in prior work by asking patients what physicians do that helps them feel cared for. Methods Topic modelling analysis was employed to identify empirical commonalities in the text responses of 767 patients describing physician behaviours that led to their feeling cared for. Results Descriptively, seven meaningful groupings of physician actions experienced as compassion emerged: listening and paying attention (71% of responses), following‐up and running tests (11%), continuity and holistic care (8%), respecting preferences (4%), genuine understanding (2%), body language and empathy (2%) and counselling and advocacy (1%). Conclusion These findings supplement prior work by identifying concrete actions that are experienced as caring by patients. These early data may provide clinicians with useful information to enhance their ability to customize care, strengthen patient-physician relationships and, ultimately, practice medicine in a way that is experienced as compassionate by patients. Public Contribution This study involves the analysis of data provided by a diverse sample of patients from the general community population of New Zealand.